Abusing the Law: The Impact of Broad Based Black Economic Empowerment Fronting on Sustainable Business - Meyer, Chantelle Heather (Stellenbosch : Stellenbosch University, 2026)
Thesis (MPhil)--Stellenbosch University, 2026.